Peran Notaris Dalam Membacakan Akta Otentik Bilamana Penghadap Tunarungu - Pramayanti, Putu Shinta Dewi; Manik, Amethysa Karama Cupu; Kusuma, Teresa Cindy; Atyarisma, Zahra Adinda (Acta Comitas : Jurnal Hukum Kenotariatan, 2024)
The aim of this journal is to understand the skills of deaf persons as presenters in making authentic deeds and to understand the role of notaries in explaining the contents of deeds to deaf persons. The aim of this research is to answer questions related to law by conducting normative legal research that combines a statutory approach with a legal concept approach to study and analyze sources based on theories, concepts, legal principles and mandatory legal regulations. The findings of this research show that deaf people are said to be competent in carrying out legal actions if they fulfill the elements of competence in the antinomy of Article 1330 of the Criminal Code, namely they are adults and not under guardianship. The determination that a deaf person is incompetent is determined based on a district court determination. Referring to the provisions in Article 43 of the Amendment Law on Notary Positions where the notary is required to translate or explain the contents of the deed in a language that is understood by the person present. However, the explanation of the article only stipulates that if the person present does not understand Indonesian, the Notary is obliged to provide a translator. Until now, the provisions of this article only accommodate language if the addressee is someone with normal conditions, there is no reference regarding the qualifications of the term sign language interpreter, especially in Indonesia.